Phenotypic Description of Theobroma cacao L. for Yield and Vigor Traits From 34 Hybrid Families in Costa Rica Based on the Genetic Basis of the Parental Population - Mustiga, Guiliana M.; Gezan, Salvador A.; Phillips-Mora, Wilbert; Arciniegas-Leal, Adriana; Mata-Quirós, Allan; Motamayor, Juan C. (Frontiers in Plant Science, 2018)
A comprehensive understanding of the genetic basis of target traits in any crop is critical to design breeding strategies that align with farmers needs for the development and release of new improved varieties. In this study, 34 cacao families were evaluated for vigor and yield related traits over the course of six years in Costa Rica. Linear mixed models provided the variance components for the partitioning of additive and non-additive effects. Heritabilities of yield over time ranged from 0.085 to 0.576, from 0.127 to 0.399 for vigor, and 0.141 to 0.146 for disease resistance traits. Significant (p < 0.001) general combining abilities were observed for ICS-43 and LcTeen-37 with negative effect on average yield (-0.674,-0.690), respectively. Specific combining abilities for yield had significant (p < 0.001) positive effect from the cross GU-154-L x UF-273 Type 2 (0.703) and strong negative interaction between ICS-43 and LF-1 (-0.975). A weighted index was used to select the top performers while providing the corresponding genetic gains. At a 1% selection intensity, yield component gains ranged from 17.8% to 331.9%. Agronomic traits such as branch angle, trunk diameter and jorquette height had lower genetic gains and lower heritabilities. In addition, the parents in this study were genotyped with a 96-SNP marker off-typing set and a significant positive correlation of 0.39 (p = 0.019) was found between genetic distance and specific combining abilities for yield. Preliminary comparison of clonal parents vs. seedlings yield in the family with the highest SCA suggest for the first time presence of heterobeltiosis in cacao.